Posttonsillectomy Pain Relief and Wound Healing by Applying Bismuth Iodoform Paraffin Paste (BIPP) to Dissected Tonsillar Beds - Idris, Rahimah; Ramli, Ramiza Ramza; Yaacob, Wan NorSyafiqah W; Hassan, Shahid (International Archives of Otorhinolaryngology, 2024)
Introduction Tonsillectomy is one of the most common operations performed by otorhinolaryngology surgeons worldwide; however, the insufficient quality of the postoperative pain management and effective posttonsillectomy pain relief remain a clinical dilemma.Objective To evaluate the efficacy of applying bismuth iodine paraffin paste (BIPP) to the dissected fossa as an adjuvant therapy for a better outcome in terms of posttonsillectomy pain management and due to its wound healing properties.Methods The present is a prospective randomized control pilot study with 44 patients aged > 7 years who underwent tonsillectomy. The patients were divided into two groups: the control group and the group that had BIPP applied to the dissected tonsillar fossa. The visual analogue scale score and the post-onsillectomy percentage of tonsillar fossa epithelization were recorded and evaluated.Results Both subjectively and objectively, there a was statistically significant pain-relieving effect in the BIPP group within the first 5 postoperative days (p < 0.05). From postoperative day 3 onward, the dissected area of the tonsillar fossa healed significantly faster in the BIPP group compared with the control group, and it became stable on day 14.Conclusion The topical application of BIPP showed a better pain-relieving effect, it was safe, and hastened wound healing after tonsillectomy.
Keywords: palatine tonsil; tonsillectomy; pain; wound healing; bismuth paste